Math skill growth and learning differences in higher education: Can lower-skilled students catch up? - Stefan Büchele; Carina Marten (Philipps-University Marburg, School of Business and Economics, 2022)
Studies determining students' success in higher education mostly rely on students' predetermined baseline variables like high school GPA or ACT scores and, therefore, describe skill differences at the beginning of college but not the development of these differences over time. Whether ex-ante lower-skilled students can catch up or higher-skilled students may expand their initial lead remains unclear. We investigate the students' learning growth in a business math course and analyze if the gap between initially higher and lower-skilled students changes. Also, we provide possible reasons for different skill growth rates using panel data and mixed-effects models. The results suggest that ex-ante higher- skilled students become disproportionately better (cumulative learning pattern). However, we find evidence that this is only because of engagement effects. In other words, ex-ante lower-skilled students cannot catch up and fall behind even more because they seem less engaged in their studies than higher-skilled students.
Keywords: 330; math skill; learning growth; higher education; learning differences; student heterogeneity